Simulation of Cattle Stomach Processes Applied to the Fermentation of Mixed Manure and Straw - Enhai Liu; Zhanghui Guo; Yali Shi; Biao Qi; Yu Wang; Yine Jiang (BioResources, 2022)
The cattle stomach was considered as the basis for simulating a proposed operation. Microenvironmental degradation mechanisms are understood to be key to the efficient utilization of straw and other resources. Through dynamic tracking of the change law of heat generated by microbial degradation of straw in the cattle stomach, this study used an orthogonal test to explore the optimal ratio of feeding feed, the degradation mechanism in the microenvironment, and the characteristics of cattle manure and straw anaerobic fermentation. The results showed that the number of days of fermentation and the ratio of straw and cattle manure had a significant impact on methane gas production, and the mixture ratio was 1:3, at 26 °C; within 20 days, the cumulative gas production was up to 78.9 L. The results also showed that rumen microorganisms, cattle manure, and mixed straw fermentation can be used at different ratios to obtain the change of methane production, and determine the best ratio to achieve the maximum gas production.